Note that in composite functions :
![(g\circ h)(x)=g(h(x))](https://img.qammunity.org/2023/formulas/mathematics/college/chzicr6qr3e29blgexz6ruinq8zm4vk463.png)
g of h of x can be written in the expression above.
From the problem,
g(t) = t + 5
h(t) = 3t - 2
Find (g o h)(-4 + t)
First step is to evaluate h(-4 + t) using the function h in the given :
![\begin{gathered} h(t)=3t-2 \\ h(-4+t)=3(-4+t)-2 \\ =-12+3t-2 \\ =-14+3t \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/eo1ev01lpuyldgxgfuznz1cvldjgobg8t7.png)
Next step is to evaluate g(-14 + 3t) which is the result in function h.
![\begin{gathered} g(t)=t+5 \\ g(-14+3t)=(-14+3t)+5 \\ =-9+3t \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/3sf9jcc2g2p0dbzt4h3z0mjr15dk38eiq8.png)
Therefore, the answer is -9 + 3t or 3t - 9